Posterior chamber volume does not change significantly during dilation. Issue 11 (4th February 2009) - Dorairaj, S; Liebmann, J M; Tello, C; Barocas, V H; Ritch, R
Abstract : Background/aims: To determine whether the volume of the posterior chamber changes during pupillary dilation. Methods: Eyes with anatomically narrow angles underwent ultrasound biomicroscopy of the posterior chamber and pupillary margin under dark- and light-room conditions to assess changes in posterior chamber anatomy and volume. All examinations were stored as real-time video. A frame-by-frame analysis was performed using a macro written for the ImageJ image-processing software. Results: Thirteen eyes were assessed. The mean patient age was 63.0 (SD 10.0) years, and the mean refractive error was 1.1 (1.9) dioptres. The horizontal mean pupillary diameter was 2.3 (0.6) mm and 3.5 (0.5) mm under light- and dark-room conditions, respectively (p<10 −7, paired t test). The mean posterior chamber volumes were unchanged under light and dark conditions (3.76 (1.09) vs 3.63 (0.78) mm 3, p = 0.22, paired t test). Volumes were greater under light conditions in eight eyes and under dark conditions in five eyes. Conclusions: The volume of the posterior chamber does not change significantly during dilation.